DA‐EPOCH‐R for post‐transplant lymphoproliferative disorders. (13th July 2017) - DeStefano, Christin B.; Malkovska, Vera; Rafei, Hind; Shenoy, Aarthi; Fitzpatrick, Kelly; Aggarwal, Anita; Catlett, Joseph P.
Abstract: Background: Post‐transplant lymphoproliferative disorders (PTLD) are a potentially fatal group of neoplasms arising in an immunodeficient environment. Although the cornerstone of treatment is reduced immunosuppression (RI), advanced cases often warrant treatment with chemoimmunotherapy. The chemoimmunotherapy regimen of dose‐adjusted (DA)‐EPOCH‐R is superior to R‐CHOP in HIV associated aggressive lymphomas, suggesting that it might also be favorable in the setting of PTLD. Methods: We performed a retrospective analysis of patients with advanced monomorphic PTLD treated with first line DA‐EPOCH‐R in addition to RI at our institution from 2003‐2016. Results: Seven patients were included. Mean age was 51 and mean time from transplant to diagnosis was 71 months. Six of the seven patients received a kidney transplant, six had stage III or IV disease, six had tumors that were EBV positive, and six completed therapy. All six patients who completed therapy achieved a complete response. Mean PFS and OS were 46.6 and 52.6 months, respectively. Treatment was well‐tolerated with no significant treatment related morbidity or mortality. Conclusions: Our findings support several observations in the literature that DA‐EPOCH‐R is efficacious and well‐tolerated for the treatment of advanced, monomorphic PTLD.